A mobile educational tool designed for teaching and dissemination of grid connected photovoltaic systems. (June 2019) - Torres, Pedro Ferreira; Costa, André Felipe Pacheco; Chaar Junior, Vilson Lima; Monteiro, Weslley Leão; Galhardo, Marcos André Barros; Pinho, João Tavares; Macêdo, Wilson Negrão
Abstract: Many developing countries that are recently incorporating distributed grid connected photovoltaic systems (GCPVSs) into their electric grid, have a deficit of specialized institutions to carry out activities of teaching, research and training people on this application. Training tools that provide hands-on experience on GCPVSs, allowing the measurement of important parameters in this application, are significant sources of dissemination of this technology. In this context, a mobile, cost-effective, training tool, known as GCPVS-MT (GCPVS-Mobile Trainer), has been developed with the purpose of assisting in training courses, academic activities and disseminating the application. This paper describes the design of the tool and discusses its utilization, providing examples of its usage in measuring important characteristics of a GCPVS. The paper presents an evaluation of the uncertainty associated with measurements of the tool and a survey assessment with students that used the trainer, making possible to evaluate its effectiveness as an educational tool.